Programming in the Complex: Cybernetic Insights into Software Process and Architecture. - Donaires, Omar Sacilotto (Systems Research & Behavioral Science)
The writer discusses the concept of programming in the complex to designate the maintenance and development of complex software systems in circumstances where the software architecture and software processes need to change dynamically to cope with the impact of frequent and unpredicted environmental changes. He proposes a systemic-cybernetic process model which is a combination of Barry Boehm's spiral model and Stafford Beer's viable system model (VSM). He discusses four relevant insights on the results of the application of VSM.